PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK PADA MATERI SPLTV DI KELAS X SMA - Dedi Ardiansyah; Yulis Jamiah; Dian Ahmad (Universitas Tanjungpura, 2019)
Abstract This research aimed to know the effectiveness of the Pair Check type cooperative learning model on SPLTV material at class X SMA Negeri 3 Pontianak. The indicators that want to be knowed are the implementation of learning management, student learning activities, student learning outcomes and student responses. The research method used was the experimental method, with a pre-experimental design. The research subjects were students of class X IPA 4. Based on data analysis from four indicators, namely: 1) the implementation of learning management was categorized well with an average score of 3.35; 2) the learning activities of students are classified as active, namely 74%; (3) classical learning outcomes of students are not met, there are only 25 students or 74% who achieve a minimum completeness value; 4) the response of students is in the positive category, with 2 students (6%) giving a very positive response, 31 students (91%) giving a positive response and 1 student (3%) responding hesitantly. So the conclusion of this study was that the application of the Pair Check type cooperative learning model is not effective on SPLTV material in class X of SMA Negeri 3 Pontianak Keywords: Cooperative learning model, Pair Check type, System of linear equations three variables